ChemInform Abstract: 3‐Carboxy‐pyrazolinalanine as a New Scaffold for Developing Potent and Selective NMDA Receptor Antagonists. Issue 12 (25th March 2014) - Tamborini, Lucia; Pinto, Andrea; Mastronardi, Federica; Iannuzzi, Maria C.; Cullia, Gregorio; Nielsen, Birgitte; De Micheli, Carlo; Conti, Paola
Abstract A synthetic method is presented for the preparation of title compounds (II) and (III) which may serve as starting material for new N‐substituted derivatives such as (VI) or (VII).